Knowledge of Dental Brushing From the Status of Dental Hygiene of Students of 1 Public Elementary School Banda Dua Pidie Jaya District - Intan Liana; Reca (Institute of Computer Science (IOCS), 2022)
One of the efforts to improve dental and oral health is by maintaining dental and oral health. However, people often ignore dental and oral health problems caused by lack of dental and oral health knowledge. This study aims to determine the knowledge about brushing teeth in terms of dental and oral hygiene status in fifth grade students of 1 Public Elementary School Banda Dua, Pidie Jaya Regency, this research was conducted using quantitative methods with a descriptive approach. Sampling using total sampling, namely all students 1 Public Elementary School Banda Dua, totaling 30 students, through interview using a questionnaire. Data analysis used univariate analysis. The results showed that the majority of students' knowledge about brushing teeth was not good, namely 20 people (67%). Most of the school students already know the benefits of keeping teeth and mouth clean to keep teeth healthy (67%), and brushing teeth before going to bed is very necessary to do (33%).